Agriculture in Lydenburg, 1900-1960 - Schirmer, Stefan (My University, 1994)
Historians opposed to structural analysis and working with models that place a greater emphasis on human agency have argued that white fanners were always highly stratified. For the period before 1930, a number of studies demonstrated that this was indeed the case, but very little detailed analysis emerged to show that stratification continued after 1930, into the 1990s. Instead, despite some statistical analyses showing that 20 per cent of white farmers produced 70 per cent of output throughout the 1950s, the literature is still dominated by assertions that ‘white farming’ became ‘capitalist’ or ‘experienced an agricultural revolution’ sometime between 1930 and I960. These approaches are unsatisfactory, because they ignore the majority of white farmers who made only small contributions to agriculture's GDP. Although many of these farmers experienced structural transformations, they did not become ‘capitalist farmers’, nor did they fully participate in an ‘agricultural revolution’. These farmers remained dependent on state aid and cheap labour, and their inability to become independent profit maximisers has had important consequences for South Africa's current transformation. It has provided the economic context for many farmers’ right-wing allegiances. This paper attempts to make a contribution towards a more stratified picture of white farming. It focuses on the district of Lydenburg, where most whites today appear to support the notion of a ‘boere-staat’ The paper argues that districts like Lydenburg must be differentiated from more productive districts elsewhere in the Transvaal. Further, farmers within Lydenburg were also stratified, which meant that changes in the district always had an uneven impact. From this perspective rural transformations were not homogenous phenomena imposed from above. Every change was contested at a number of levels: by white farmers threatened by the growing dominance of the market, and by Africans seeking to maintain access to land. The paper focuses on how economic processes transformed Lydenburg. From 1902 the district was gradually integrated more fully into the wider South African economy, and experienced spurts of growth that raised most farmers' standard of living. However, the paper shows that farmers did not benefit equally from this growth. Some farmers were always more ready to take risks, and thus benefited the most, while others remained cautious, failed to expand their enterprises, and struggled to retain their land. A growing number of these farmers eventually gave up this struggle and moved to the urban areas. The paper also demonstrates that both economic accumulation and attempts to retain land in the face of hostile market forces were dependent on various forms of state aid.
African Studies Seminar series. Paper presented 16 May 1994
Keywords: Agriculture. Economic aspects. South Africa. Lydenburg District